The Effectiveness of Using Wall Word Media in Teaching Vocabulary for EFL Young Learners - Hasan, Jhems Richard; Habibie, Alvons (Journal of English Teaching and Linguistic Issues (JETLI), 2023)
This study aims to examine the effectiveness of wall word media in improving students’ vocabulary mastery in SMP Negeri 1 Paguyaman, Gorontalo. Quantitative methods are research approaches that involve the collection and analysis of numerical data to answer research questions or test hypotheses. This method emphasizes the use of statistical analysis to examine relationships between variables and to determine the significance of results. A quasi-experiment is a research design used in this study. This indicates that the use of Wall Word media can improve English vocabulary mastery in students. After exploring the use of Wall word Media in teaching vocabulary to young learners, it can be concluded that this media can be an effective and engaging way to enhance students' vocabulary learning. The visual and interactive nature of Wall word Media can help young learners to remember new words more easily and retain them for longer periods. Furthermore, the tool can be used to introduce learners to different cultures and help them to develop their understanding of diverse perspectives. It is worth noting, however, that Wall word Media should not be used in isolation as the sole method of teaching vocabulary.